Successful endonasal dacryocystorhinostomy in a patient with Wegener’s granulomatosis - Eloy, P (Dove Medical Press, 2009)
Wegener’s granulomatosis (WG) is one form of idiopathic autoimmune vasculitis. The disease has a predilection for the upper and lower respiratory tracts (lungs, nose, sinus), and kidneys. WG may be systemic, severe, and potentially lethal, but it may also be limited to the otolaryngological area or to the eyes and the orbits. Obstruction of the lacrimal pathway is a possible complication of the disease that affects approximately 7% of patients with WG. It usually occurs as a direct extension of sinonasal disease and typically is a late manifestation. Management of such a condition is generally viewed as difficult. We report the case of a patient with a quiescent WG limited to the otolaryngological area. This patient presented a bilateral obstruction of the nasolacrimal ducts caused by bilateral extensive adhesions in the nasal cavity. Because she had several episodes of left-side acute dacryocystitis which necessitated several courses of broad-spectrum antibiotics, she successfully underwent an endonasal endoscopic dacryocystorhinostomy using a diode laser and powered instrumentation. The authors describe the clinical case, the surgical technique, and review the literature.